Analysis of Chitin, Chitosan, and Optimization for Carotenoids Extraction Yield with Rice Bran Oil from Thai Fairy Shrimp - Tanyarat Poothawan (Science Faculty of Chiang Mai University, 2019)
This work was aimed to analysis chitin and chitosan in Thai fairy shrimp (Streptocephalus sirindhornae Sanoamuang, Murugan, Weekers and Dumont, 2000), and to optimize carotenoids extraction yield with vegetable oil using response surface methodology. Chitin was extracted from frozen fairy shrimp through the processes of demineralization and deproteinization. The experiment showed that Thai fairy shrimp constitutes chitin at 4.5%. Chitosan derived from chitin treated with 60%NaOH solution showed the highest %DDA at 86.13%. Fairy shrimp chitin and chitosan were characterized by FT-IR, XRD, TGA, and SEM. The results of studied demonstrate that fairy shrimp chitosan was similar to referenced chitosan derived from shrimp. Furthermore, optimization for carotenoid extraction using rice bran oil was also investigated. The optimized condition for carotenoids yield from dried fairy shrimp was sample to oil level ratio at 0.08g/ml, at 56.5 °C for 41.25 min. All result showed the new chitin and chitosan source that could be used in food and drug applications. The carotenoids extraction from fairy shrimp with vegetable oil would be applied in processed food industries to increase the value added from Thai fairy shrimp.